2019
DOI: 10.1016/j.nbd.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging biomarkers of epileptogenecity after traumatic brain injury – Preclinical frontiers

Abstract: Posttraumatic epilepsy (PTE) is a major neurodegenerative disease accounting for 20% of symptomatic epilepsy cases. A long latent phase offers a potential window for prophylactic treatment strategies to prevent epilepsy onset, provided that the patients at risk can be identified. Some promising imaging biomarker candidates for posttraumatic epileptogenesis have been identified, but more are required to provide the specificity and sensitivity for accurate prediction. Experimental models and preclinical longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 114 publications
(137 reference statements)
1
14
0
Order By: Relevance
“…The challenge is to identify biomarkers for these processes and target interventions. Imaging markers such as gradient echo MRI for blood products or diffusion tensor MRI for pathway remodelling, evidence of thalamic or hippocampal damage may help to stratify risk [ 29 ]. Genetic markers help stratification of the interaction between acquired and constitutional risk.…”
Section: Prevention Of Seizures and Epilepsymentioning
confidence: 99%
“…The challenge is to identify biomarkers for these processes and target interventions. Imaging markers such as gradient echo MRI for blood products or diffusion tensor MRI for pathway remodelling, evidence of thalamic or hippocampal damage may help to stratify risk [ 29 ]. Genetic markers help stratification of the interaction between acquired and constitutional risk.…”
Section: Prevention Of Seizures and Epilepsymentioning
confidence: 99%
“…Microstructural hippocampal changes are of particular interest, as the dentate gyrus in TBI rats has shown to be particularly susceptible to generating self-sustaining epileptic activity following stimulation compared with controls. 48 DTI abnormalities may thus reveal biomarkers of epileptogenic etiology unique from injury. FA and axial, radial, and mean diffusivities were each altered following both SE and TBI, where changes followed a gradient: SE > ipsilateral to TBI > contralateral to TBI.…”
Section: Dti Highlights Structural Plasticity In Preclinical Modelsmentioning
confidence: 99%
“…47 LFP models have also proposed that mossy fiber sprouting in the dentate gyrus of the hippocampus is associated with increased seizure susceptibility, suggesting that network plasticity may be a mechanism of spontaneous seizure generation. 48 DTI abnormalities may thus reveal biomarkers of epileptogenic etiology unique from injury.…”
Section: Dti Highlights Structural Plasticity In Preclinical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in gray matter and white matter related to epilepsy have been widely observed by using structural MRI (Immonen et al, 2018;Shah et al, 2019;Lutkenhoff et al, 2020). Many recent studies have shown that machine learning techniques and multiplex networks applied to completely non-invasive neuroimaging techniques, such as structural MRI, can be useful and efficient to detect pathological alterations in several neurological diseases, such as Alzheimer's disease, Parkinson's disease, and epilepsy (Amoroso et al, 2018c;La Rocca et al, 2018;Bharath et al, 2019).…”
Section: Introductionmentioning
confidence: 99%